Faktor-Faktor yang Mempengaruhi Pendapatan Petani Ikan Kolam di Desa Haur Gading - Maulana, Muhammad Rizka; Fahlevi, Khairi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Fisheries potential contained in Hulu Sungai Utara District into its own record in anattempt to boost a greater role in the economy Hulu Sungai Utara District. Besides this,the human resources to move the fishery sector has to prospect for development. Becausethe fishery potential is very large and is supported by natural resources is great, but theproduction of the fisheries sector is still relatively small, so to the need for policies thatcan encourage to increase fish production in the particular subsector of aquaculture inHulu Sungai Utara and indirectly will improve people’s welfare especially fish farmers.This study aims to determine what factors are some influence on farmers’ incomefish pond, method of this study is research that is descriptive quantitative research objectincome of farmers in HaurGading Village research object income of farmers inHaurGading Village using this type of primary data obtained from interviews of all fishfarmers fish pond with a population of 32 respondents and secondary data obtained fromthe relevant agencies.The result showed that the factors of land, feed, seed, and drugs affect concurrentlyor simultaneislyti the farmer's income fish pond, and there are factors of land and seedsthat are partially significant effect on the income of farmers fish pond in HaurGadingDistrict.